2011
DOI: 10.1021/cs100033v
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polymorphic ZrO2Phases and the Silver Electronic State on the Activity of Ag/ZrO2Catalysts in the Hydrogenation of CO2to Methanol

Abstract: Ag/ZrO 2 and Ag/ZrO 2 /ZnO catalysts obtained by the coprecipitation method were studied in the CO 2 hydrogenation to methanol. The catalyst structure was determined using X-ray diffraction (XRD) and Thermo-Programmed Reduction (TPR). The X-ray Photoelectron Spectroscopy (XPS) and Auger spectroscopies were used to determine the silver electronic state. It was found that selection of the appropriate conditions of the catalyst preparation influences silver dispersion degree, its electronic state, and contents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 55 publications
5
61
0
Order By: Relevance
“…The Zr 3d photoelectron line for all Au catalysts exhibits peak for Zr 3d 5/2 at 182.0-182.9 eV, close to that observed for Zr 4+ ions [25,30,34,36,[39][40][41]. Fig.…”
Section: Xps Analysissupporting
confidence: 72%
“…The Zr 3d photoelectron line for all Au catalysts exhibits peak for Zr 3d 5/2 at 182.0-182.9 eV, close to that observed for Zr 4+ ions [25,30,34,36,[39][40][41]. Fig.…”
Section: Xps Analysissupporting
confidence: 72%
“…However, there are few studies that indicate the opposite [46]. In the work done by Grabowski [47], Ag/ZrO 2 catalyst showed good performance in methanol synthesis. It was found that both selectivity and activity did not have any correlation with Ag 0 dispersion and content.…”
Section: Other Catalyst Systemmentioning
confidence: 99%
“…The presence of two different XPS peaks with 2.4 eV energy gap indicates the existence of two different types of zirconium ions. Lower binding energy peak at 182.2 eV ratifies the existence of Zr 4+ as ZrO 2 whereas higher binding energy peak at 184.6 eV represents Zr 2+ species [41]. Cu 2p 3/2 peak of each catalyst was resolved into different peaks to identify the different Cu species and is displayed in Fig.…”
Section: Metal-metal Interaction and Surface Analysismentioning
confidence: 99%